Pengaruh Rasio Semen/Serat Dan Jenis Katalis Terhadap Kekuatan Fiber-Cement Board Dari Limbah Kertas Kardus (The Influence of Cement-to-Fiber Ratio and Type of Catalyst on Strength Properties of Fiber-Cement Board Made from Old Corrugated Paper) - Luthfi Hakim; Tito Sucipto (FORESTA, 2012)
Fiber cement board (FCB) made from old corrugated paper has not to develop. The main objective of this study was to evaluate the suitability of old corrugated paper as reinforcement for cement-bonded board and the study was undertaken to: 1) determine the optimum cement-to-fiber ratio, the best type of catalyst; 2) determine the strength properties of cement-bonded boards manufactured from the old corrugated paper; 3) determine the effect of cement-to-fiber ratio on strength properties of cement-bonded boards from old corrugated paper. The treatments of cement/fiber ratio were 60:40 ; 50:50 and 40:60. The catalyst were aluminum sulfate (Al2(SO4)3), sodium silicate (Na2SiO3), and calcium chloride (CaCl2) as an accelerator. Old Corrugated paper was soaked into cold water for 48 hours and continued re-pulped with disintegrator at 2 % consistency for 15 minutes until the fiber separated. The boards were pressed by cold press at 25 kg/cm2 for 15 minutes with density target at 1 g/cm3. Methods of this research were two steps curing. The first step was air curing for 48 hours and continued of second step was oven curing at 80o C for 48 hours. The result of the research showed that the density of boards was average 1.03 g/cm3. The effect of cement-to-fiber ratio on the strength properties showed that 60:40 is better rather than 50:50 and 40:60. The best Catalyst is calcium chloride (CaCl2).Keywords: catalyst, fiber-cement board, old corrugated paper, strength properties.